Surgery for Deformities of the Thoracic Wall: No More than Strengthening the Patient's Self-Esteem? - Fortmann, Caroline; Petersen, Claus (European Journal of Pediatric Surgery, 2018)
In most cases, correction of a pectus deformity is performed for cosmetic reasons. The main indication for corrective therapy is impaired body image and self-esteem due to the deformity. In these instances, patients suffer from a lower quality of life that is not correlated with the severity of the chest wall deformity. After correction of a pectus excavatum (PE) or pectus carinatum (PC) patients experience a significant improvement in body image and self-esteem. For many, corrective surgery is life changing as it leaves patients feeling satisfied with the appearance of their chest, and this in turn increases their engagement in social activities. As this correction is mainly performed in adolescence, the treatment has a high impact on the future of patients that is often rooted in decisions made and actions taken during puberty.
Keywords: pectus excavatum; pectus carinatum; body image; self-esteem; quality of life